2011
DOI: 10.1111/j.1542-2011.2011.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Reproductive Life Plan

Abstract: The purpose of this article is 2-fold: to emphasize the importance of a reproductive life plan and to define its key elements. We review the 2006 recommendations from the Centers for Disease Control and Prevention (CDC) regarding ways to improve the delivery of preconception health care to women in the United States, with particular focus on encouraging individual reproductive responsibility throughout the life span and on encouraging every woman to develop a reproductive life plan. We propose recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 32 publications
(56 reference statements)
1
36
0
Order By: Relevance
“…We expect findings from this study could also be of global interest. A specially designed booklet, such as the one we developed for this study, or an educational hand-out (Files et al , 2011), is easy to adapt to other populations and can be used by health care providers with limited time for consultations (Dunlop et al , 2007). However, the implementation of the RLP concept and the effect needs to be confirmed through further studies and we are now expanding our project to other parts in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…We expect findings from this study could also be of global interest. A specially designed booklet, such as the one we developed for this study, or an educational hand-out (Files et al , 2011), is easy to adapt to other populations and can be used by health care providers with limited time for consultations (Dunlop et al , 2007). However, the implementation of the RLP concept and the effect needs to be confirmed through further studies and we are now expanding our project to other parts in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…Condoms reduce transmission of HIV, syphilis, and sexually transmitted infections in women at risk and can be used as a secondary contraceptive method to decrease the likelihood of pregnancy 2 . Contraceptive counseling is imperative before and after AEDs become part of the woman's medication regimen and should be initiated at the onset of puberty 1,3,8,13,18 . In addition, preconception counseling should be provided for women with epilepsy in order to take steps to reduce health risks and improve pregnancy outcomes 13 …”
Section: Discussionmentioning
confidence: 99%
“…Files et al. () suggested that essential elements include (a) the desire for children, (b) the age of the woman and her partner, (c) maternal health status, (d) desired number and spacing of children, and (e) examination of a woman's risk tolerance, life context, and family history. While all of these components are of obvious utility in making reproductive decisions, most of the scenarios presented in the article best pertain to educated middle and upper class women.…”
Section: Current Policy Around Preconception Care: the Cdc's Initiativementioning
confidence: 99%
“…The article goes on to suggest that the provider assess “readiness for conception” by asking “Do you have plans for conceiving a child in the next 1 to 5 years”? (Files et al., , p. 470) There is an algorithm to direct the discussion based on the age of the woman (25 and older or younger than 25) and whether she has plans for childbearing in the next 5 years (to view the full article and algorithm, go to http://onlinelibrary.wiley.com/doi/10.1111/j.1542--2011.2011.00048.x/full). This approach could work well for some women, but as we have noted, many women are ambivalent about pregnancy and providers need to be prepared to help women who may not have reproductive goals.…”
Section: Current Policy Around Preconception Care: the Cdc's Initiativementioning
confidence: 99%